2021
DOI: 10.3390/molecules26226773
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsive Effects of Chondroitin Sulfate on Pilocarpine and Pentylenetetrazole Induced Epileptogenesis in Mice

Abstract: Chondroitin sulfate is a proteoglycan component of the extracellular matrix (ECM) that supports neuronal and non-neuronal cell activity, provides a negative domain to the extracellular matrix, regulates the intracellular positive ion concentration, and maintains the hypersynchronous epileptiform activity. Therefore, the present study hypothesized an antiepileptic potential of chondroitin sulfate (CS) in pentylenetetrazole-induced kindled epilepsy and pilocarpine-induced status epilepticus in mice. Levels of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…In vivo studies have shown the potential of CS to reduce the severity of arthritis in rats [ 14 , 38 ]. Several studies show that CS may interfere with inflammatory processes by inhibition of the expression of pro-inflammatory molecules, such as interleukin- 1 beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and nuclear factor-κB (NF-kB) [ 39 , 40 ]. Based on these data, the isolated compound (CST) was tested in a peritoneal inflammatory model induced by sodium thioglycolate.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo studies have shown the potential of CS to reduce the severity of arthritis in rats [ 14 , 38 ]. Several studies show that CS may interfere with inflammatory processes by inhibition of the expression of pro-inflammatory molecules, such as interleukin- 1 beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and nuclear factor-κB (NF-kB) [ 39 , 40 ]. Based on these data, the isolated compound (CST) was tested in a peritoneal inflammatory model induced by sodium thioglycolate.…”
Section: Resultsmentioning
confidence: 99%
“…Each day, formula was made based on daily weights and the caloric needs of the pups from the batch stock and supplemented with 0.008 mg/g of Lipopolysaccharide (LPS) isolated from Escherichia Coli O111:B4 (cat # L4391, Sigma‐Aldrich Company, St. Louis, MO). Those in the group to receive chondroitin sulfate, had their formula supplemented to receive 0.2 mg/g chondroitin sulfate daily (Cimini et al, 2022 ; Gao et al, 2022 ; Qi et al, 2021 ; Singh et al, 2021 ; Song et al, 2017 ). Experimental pups were gavage fed a hyper‐concentrated formula (300 kcal/kg/day) three times per day using a 1.9 French catheter.…”
Section: Methodsmentioning
confidence: 99%
“…A certificate of analysis was provided by the company for the lot number used in these experiments. The dose of chondroitin sulfate was determined by a literature search of chondroitin sulfate doses in different rodent models of disease that all used a dose of 200 mg/kg for beneficial therapeutic effects (Cimini et al, 2022 ; Gao et al, 2022 ; Qi et al, 2021 ; Singh et al, 2021 ; Song et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dietary polysaccharides have shown potential in reducing inflammatory responses, inhibiting the expression of neurotransmission-related genes, and improving hippocampal tissue damage in epilepsy models. Due to the antioxidant and antiinflammatory properties of chondroitin sulfate, a significant reduction in seizure mice induced by pentylenetetrazole and pilocarpine was observed (105). Fructus corni polysaccharide treatment (106) decreased levels of ROS and malondialdehyde (MDA), increased superoxide dismutase (SOD) activity, and inhibited expressions of phosphorylated-Jun N-terminal Kinase (p-JNK), cytochrome C, and caspase-3 in an epileptic rat model.…”
Section: Dietary Polysaccharides and The Interventions For Epilepsymentioning
confidence: 99%